出生前ステロイド療法による胎仔腎臓の発達にプロレニン受容体とERKが関与する - 中村, 悠城; 山本, 信; 大滝, 正訓; 上條―池森, 敦子; 小林, 司; 太田, 有紀; 松本, 直樹; 木田, 圭亮; 飯利, 太朗; 渡辺, 実; 武半, 優子; 柴垣, 有吾 (日本薬理学会年会要旨集, 2019)
This study aimed to investigate whether prenatal glucocorticoid (GC) administration is associated with fetal kidney maturation. We investigated the effects on the prorenin receptor (PRR) and ERK expressions for kidney development in the fetal rats. Dexamethasone (DEX) was administered to pregnant rats for 2 days on day 17 or day 19 of gestation, and the kidney of fetuses and neonates were analyzed by immunohistochemistry. The viability of HEK 293 cells treated with DEX was determined by MTT assay, and mRNA and protein expressions of the PRR, ERK, and phospho(p)-ERK were analyzed. ERK-positive areas were observed in primitive perivascular mesenchymal cells and immature glomeruli of the fetal rats. ERK-positive areas were significantly increased in the kidneys of 21-day fetuses compared with those of 19-day fetuses. DEX tended to increase ERK- and p-ERK-positive areas in the kidney of 19-day fetuses. However, the PPR-positive areas did not change with DEX. DEX also significantly increased the mRNA and protein levels of ERK, p-ERK, and PRR in HEK293 cells. These results indicate that prenatal DEX administration may contribute to kidney development through ERK increase in the fetal rat.